A SURVEY OF BROADCASTING PROTOCOLS IN WIRELESS NETWORK (International Journal of Engineering and Computer Science, 2017)
Broadcasting is a fundamental operation in which a single message is to be sent from a source to all other nodes in the network. This paper presents a brief survey of broadcasting in wireless network and different types of broadcasting techniques. Broadcasting plays an important role in designing communication protocols in various types of networks. For example, in highly parallel systems such as Networks of Workstations (NOW) or Grid computing, it is essential to quickly distribute the input data or computational results quickly to all nodes in the system. The factors affecting the performance of the broadcasting also discussed. Different broadcasting methods have different advantages, hence a suitable method must be chosen for any application. We have discussed the advantages and disadvantages of all the method, and compared these methods on the basis of different criteria.